The Gremlins by Roald Dahl: The Reflection of his War Experiences and the Theme of War in his First Book for Children - Gámez Gómez, Ariadna (Journal of Artistic Creation and Literary Research, 2025)
This research project aims to offer an analysis of Roald Dahl's first book for children, The Gremlins (1943). The analysis will be focused on drawing connections between this book and Dahl’s own experiences during his years as a RAF pilot in World War II. And simultaneously, bearing in mind that this is a book for children, it will also be explained how the author narrates a story about war – making it suitable– for that target readers. What makes this topic relevant is that in the Literary Studies of English Studies Degree, children’s literature is often not deeply studied. Thus, this work can result interesting because it treats a topic that, as we will find out, is controversial in books for children. Additionally, it is the first bookofthiskindbyRoaldDahl,whoafterthisworkdevelopeda very successful career as a children’s author, becoming one ofthemostimportantwriters in the field. In order to carry out the analysis of the book, the principal sources used to draw the connections between his war experiences and The Gremlins (1943) will be: Dahl’s Going Solo (1986), Jeremy Treglown’s Roald Dahl: A Biography (1994), Donald Sturrock’s Storyteller: The Authorized biography of Roald Dahl (2010)andotheracademic articles, principally from The Official Roald Dahl Website. And, then, to explain how he treats the theme of war in a book forchildren,theacademicarticlesofJacquesBarchilon, “Children and War in the Fairy Tale,” Catherine Kurkjian, “Children’s Books: Worlds of Fantasy,” and Allen Newell, “Fairy Tales,” will be taken as main references.